Technology of the information and communication in public and private schools in Arequipa - Arias Gallegos, Walter Lizandro (2015)
In this study, we made a frequency and percentage analysis of TIC in Arequipa City (Peru) in order to identify the most frequent ICTs in the school context and settle a comparison between private and public schools. It was designed a survey and applied in 83 schools (51 private y 32 public) that were selected by probabilistic methods. The results suggest that access to ICTs is low in both types of schools but minor in public school. The most frequent ICTs were computer, television, DVD player, radio and the internet.